(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the views of the Turkish historian Ismail Aka on the basis of historical sources on the life and activities of Amir Timur. The role of Ismail Aka in forming the school of Temur Studies in Turkey is shown